Ensuring the sexual and reproductive health of people living with HIV : policies, programmes and health services - Lusti-Narasimhan, Manjula (2007)
Examines the synergistic roles of individuals' rights, needs and aspirations, the socio-economic context, health systems and law and policy in helping or hindering the development and delivery of adequate programmes and services for HIV positive people. Highlights the importance of the linkages between these areas for effective design and delivery of services and programmes.